2019
DOI: 10.7899/jce-18-14
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to education for chiropractic students with visual impairment

Abstract: Objective The purpose of this study was to document the academic experiences of students with visual impairment in a doctor of chiropractic program. Methods Ten participants were recruited, including 3 students who are “legally blind,” 2 student notetakers, 3 faculty members who taught students with visual impairment, and 2 staff members from the Disability Services Office. For this qualitative study, the students were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This study indicates that using tactile methods of instruction supports learning for visually impaired students in a chiropractic program. Our findings are consistent with our previous research that identified overall barriers and facilitators of learning for students with visual impairments (Joshi & Ray, 2018), and other studies that suggest that visually impaired students can successfully complete science-oriented programs when the means to acquire the requisite knowledge are provided.…”
Section: Discussionsupporting
confidence: 92%
“…This study indicates that using tactile methods of instruction supports learning for visually impaired students in a chiropractic program. Our findings are consistent with our previous research that identified overall barriers and facilitators of learning for students with visual impairments (Joshi & Ray, 2018), and other studies that suggest that visually impaired students can successfully complete science-oriented programs when the means to acquire the requisite knowledge are provided.…”
Section: Discussionsupporting
confidence: 92%
“…Perhaps the most striking point is that students with VI have faced these kinds of barriers even in developed nations such as Australia (Butler et al, 2017), Canada (Ostrowski, 2016;Reed & Curtis, 2012), the US (Joshi & Ray, 2020) and the UK (Frank et al, 2014;Orsini-Jones, 2009). The results of these studies clearly indicate that there is cause for concern about higher education for students with VI in both developed and developing nations.…”
Section: Review Of Related Literaturementioning
confidence: 93%
“…Notable facilitators included planning for accessible educational materials, accessibility of workable space, and availability of support systems, such as note-takers. Notable barriers included the attitudes of students with VI toward their education, lack of personnel training, and lack of disability awareness in the campus community (Joshi & Ray, 2020).…”
Section: Review Of Related Literaturementioning
confidence: 99%